Structure of regulation: Lessons from the crisis. A view from the Institute of International Finance (IIF) - Dallara, Charles (Journal of Financial Stability, 2008)
The IIF's Committee on Market Best Practices has been working on five subjects: (1) Risk management, realignment of incentives is necessary; (2) Ratings, an SRO for CRAs is proposed; (3) Valuations, more dialogue on processes; (4) Disclosure, some new initiatives; (5) Liquidity risk, a review is in hand. Regulation's enforcement intensity is not a good measure of effectiveness; instead a more supervisory, risk-based approach is desirable. There is a need for a framework of mutual recognition in the context of cross-border regulation, with greater use of colleges of supervisors. Within Europe a start would involve putting the Level 3 Committees onto a stronger legal basis.